2000
DOI: 10.1086/302700
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SLC7A7 Gene and Mutational Analysis of Patients Affected by Lysinuric Protein Intolerance

Abstract: Lysinuric protein intolerance (LPI) is a rare autosomal recessive defect of cationic amino acid transport caused by mutations in the SLC7A7 gene. We report the genomic structure of the gene and the results of the mutational analysis in Italian, Tunisian, and Japanese patients. The SLC7A7 gene consists of 10 exons; sequences of all of the exon-intron boundaries are reported here. All of the mutant alleles were characterized and eight novel mutations were detected, including two missense mutations, 242A-->C (M1L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
5
47
1
Order By: Relevance
“…Mutational screening of the whole coding region and all intron/exon boundaries was performed by PCR and direct sequencing, with PCR conditions and primers reported earlier. 3 The promoter localized in intron 1, which is the active promoter in tissues with strong defects in LPI patients, 16 was also amplified with primers (5 0 -CTGGCCTGATTTCCTCATATT-3 0 ) and [5 0 -GAGGGTTAGCAAGGTAAGTGG-3 0 ), following standard methods. The reaction started with an initial denaturation of 5 min at 941C, followed by 36 cycles of 941C 30 s, 581C 30 s, 741C 1 min and 5 min at 741C.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational screening of the whole coding region and all intron/exon boundaries was performed by PCR and direct sequencing, with PCR conditions and primers reported earlier. 3 The promoter localized in intron 1, which is the active promoter in tissues with strong defects in LPI patients, 16 was also amplified with primers (5 0 -CTGGCCTGATTTCCTCATATT-3 0 ) and [5 0 -GAGGGTTAGCAAGGTAAGTGG-3 0 ), following standard methods. The reaction started with an initial denaturation of 5 min at 941C, followed by 36 cycles of 941C 30 s, 581C 30 s, 741C 1 min and 5 min at 741C.…”
Section: Patientsmentioning
confidence: 99%
“…12 -15 It contains 11 exons (9 coding exons), 10 introns and two promoter regions spanning B46.5 kb of the genomic DNA. 3,4,16 The cDNA is 2477 bp long with a 527 bp 5 0 -UTR and a 385 bp 3 0 -UTR, with a polyA site located at 2447. 6 It encodes the y þ LAT1 protein (RefSeq: NP_003973), which has 511 predicted amino acids and a molecular weight of B56 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…9 Direct sequencing was carried out on PCR products and both strands were sequenced by an automated system (ABI 377 DNA, Applied Biosystems, Monza, Italy).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…The variability of the phenotype cannot be explained by either a straightforward correlation with the genotype or variable compliance to the therapy. 9,10 For example, two of the most severe genotypes reported so far, that is, homozygosity for a large deletion of the gene (patient IV-2, family 1 in Borsani et al 2 ) or homozygosity for the M1L mutation (patients 1A and 1B in Sperandeo et al 9 ), both of which result in absent protein, were found in patients with a very mild phenotype under treatment. The ubiquitous expression of SLC7A6 and the overlapping transport activity suggest that y þ LAT-2 may compensate when y þ LAT-1 is defective.…”
Section: Introductionmentioning
confidence: 99%
“…All exons and intron-exon boundaries of the SLC7A7 gene were amplified from genomic DNA extracted from peripheral blood samples of all family members as previously reported (Sperandeo et al, 2000). Direct sequencing was performed on two distinct PCR products, and both strands were sequenced by an automated system (ABI 377 DNA, Applied Biosystems, Monza, Italy).…”
Section: Mutation Analysismentioning
confidence: 99%